From Form to Content: A Study of Abbas Nalbandian’s Impact on the Iranian Theatre of the Absurd [In Persian] - Omid Delbandi (زبان کاوی کاربردی)
The Theatre of the Absurd, also known as Absurdist Theatre, is one of the prominent modernist movements in 20th-century drama. It emerged in the aftermath of World War II, shaped by deep philosophical, social, and political crises. This theatrical style reflects the existential anxiety of modern humans when faced with an incomprehensible and chaotic world. What distinguishes Absurdist Theatre from earlier dramatic traditions is not only its themes, but also its formal innovations—such as the abandonment of conventional narrative structures, the use of characters without defined psychological or social backgrounds, and dialogue that is often fragmented, repetitive, or illogical. In Iran, the rise of translated works and the influence of Western modernist thought during the 1960s and 1970s encouraged a new approach to the recreation of absurdist form and content. This development provided Iranian playwrights with a fresh framework for expressing existential and social anxieties. Among them, Abbas Nalbandian stood out for his experimental use of language—blending literary, colloquial, and distorted vocabulary—along with syntactic disruption, deliberately lengthy titles, and even intentional spelling errors. Through these techniques, he sought to depict the fragmented, unstable, and ironically humorous experience of the Iranian individual confronting modernity. This article focuses on two of Nalbandian’s plays—A Deep and Magnificent Research… and If Faust Had a Bit of Insight…—to analyze how absurdist elements are integrated with Iran’s unique linguistic, cultural, and social structures. As a pioneering and innovative modern playwright, Nalbandian played a key role in shaping and expanding Iran’s Theatre of the Absurd. By developing original dramatic forms, incorporating Iranian cultural references, and raising philosophical questions rooted in the Iranian context, he forged a distinctive style—one that is not a mere imitation of Western absurdism, but rather a creative, localized reinvention of the genre. Despite the structural and aesthetic significance of his work, Nalbandian’s plays have gradually faded from public attention. This decline can be attributed to broad lifestyle changes in Iranian society, the constraints of official publishing channels, and the lack of continued critical engagement with his work.